2017
DOI: 10.1371/journal.pone.0183259
|View full text |Cite
|
Sign up to set email alerts
|

A physiological model for interpretation of arterial spin labeling reactive hyperemia of calf muscles

Abstract: To characterize and interpret arterial spin labeling (ASL) reactive hyperemia of calf muscles for a better understanding of the microcirculation in peripheral arterial disease (PAD), we present a physiological model incorporating oxygen transport, tissue metabolism, and vascular regulation mechanisms. The model demonstrated distinct effects between arterial stenoses and microvascular dysfunction on reactive hyperemia, and indicated a higher sensitivity of 2-minute thigh cuffing to microvascular dysfunction tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…10,12 This study suggested that the shape of reactive hyperemia perfusion response may reflect multiple aspects of the pathophysiology, potentially including both macroand microvascular damage, and a more sophisticated analysis such as the model-based approach may be valuable. 15 The arterial resistance increased with symptom severity in the bilateral comparison and in the comparison between severity groups, and the standard macrovascular assessment by the ABI agreed with these results. On the other hand, we speculate that the "microvascular" indices reflect microvascular dysfunction.…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…10,12 This study suggested that the shape of reactive hyperemia perfusion response may reflect multiple aspects of the pathophysiology, potentially including both macroand microvascular damage, and a more sophisticated analysis such as the model-based approach may be valuable. 15 The arterial resistance increased with symptom severity in the bilateral comparison and in the comparison between severity groups, and the standard macrovascular assessment by the ABI agreed with these results. On the other hand, we speculate that the "microvascular" indices reflect microvascular dysfunction.…”
Section: Discussionsupporting
confidence: 64%
“…The peak perfusion and model resistance reflected the macrovascular disease burden in accord with the results assessed by the ABI. As explained in the previous work, 15 the response characteristics in longer durations of flow arrest may be less specific to any particular microvascular regulatory mechanism. Furthermore, measures of macrovascular resistance were found to be related to the manifested symptom severity, whereas microvascular function seemed to be related to prognosis following revascularization.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations